Phytase Activity in the Grain of 6 Varieties of Wheat Cultivated in Kurdistan Province - Zarei, M.A. (International Journal of Poultry Science, 2007)
Phytase improves the bioavailability of phytate phosphorous in plant foods and reduces phosphorous pollution of animal waste. Purpose of this study was to determine phytase activity in the grains of different varieties of wheat as a part of poultry diet. Grain samples were ground with mill and passed through 0.5 mm sieve, then mixed thoroughly and dissolved in food buffer. The top layer was filtered through PVDF filters. Definite volumes of filtrate dissolved in Dilution buffer and incubated with substrate for 60 minutes at 37 °C. After 10 minutes centrifugation of all samples at 5000 RPM, absorbance of supernatants was read at 415 nm. Finally phytase activity of samples was determined using the calibration curve which has been made from enzyme samples with known phytase activity. This work showed the highest Phytase activity for the Sardary variety.